Antioxidant biochemical responses to long-term copper exposure in Bathymodiolus azoricus from Menez-Gwen hydrothermal vent - Company, Rui (2020)
Copper (Cu) is essential to various physiological processes in marine organisms. However, at high concentrations this redox-active transition metal may enhance the formation of reactive oxygen species (ROS) and subsequently initiate oxidative damage. High concentrations of Cu may increase oxidative damage to lipids, proteins and DNA. Bathymodiolus azoricus is a Mytilid bivalve very common in hydrothermal environments near the Azores Triple Junction continuously exposed to high metal concentrations, including Cu, emanating from the vent fluids. The knowledge of antioxidant defence system and other stress related biomarkers in these organisms is still scarce. The aim of this work was to study the effect of Cu (25 microg l(-1); 24 days exposure; 6 days depuration) on the antioxidant stress biomarkers in the gills and mantle of B. azoricus. The expression of stress related biomarkers was tissue-dependent and results suggest that other factors than metal exposure may influence stress biomarkers, since little variation in antioxidant enzymes activities, MT concentrations, LPO and total oxyradical scavenging capacity (TOSC) occurred in both control and Cu-exposed mussels. Moreover, there is a general tendency for these parameters to increase with time, in both control and Cu-exposed mussels, suggesting that reactive oxygen species (ROS) formation is not metal dependent, and may be related with poor physiological conditions of the animals after long periods in adverse conditions compared to those in hydrothermal environments.